Jaringan Komputer Quantum dan Penerapan Quantum Key Distribution pada Keamanan Data Perbankan - Putra, Fadhil Adiyatma; Setiaji, Bayu Isma; Syafri, Ahmad Nur (Journal of Information Systems and Business Technology, 2025)
The development of quantum computing has a significant impact on cybersecurity, particularly in the banking sector, which relies heavily on data confidentiality and integrity. Classical cryptographic algorithms are at risk of becoming vulnerable due to the ability of quantum computers to break encryption systems using algorithms such as Shor's, raising the need for new security technologies based on quantum mechanical principles. This study analyzes the concept of quantum computer networks, identifies implementation challenges, and examines case studies of Quantum Key Distribution (QKD) applications in banking data security systems. The research method used is a descriptive approach through literature analysis and case studies of QKD applications in global financial networks. The results show that QKD can improve the security of encryption key exchanges through an eavesdropping detection mechanism that relies on changes in the state of photons, thus enabling communications that are theoretically impossible to intercept without detection. Case studies of the SwissQuantum Network and financial networks in China demonstrate that the implementation of QKD has successfully improved the security of data communications between bank branches and data centers. However, this study also identified several key challenges, such as high infrastructure costs, limited transmission distances, and the complexity of integration with existing cryptographic systems and conventional networks. Furthermore, human resource readiness, regulatory support, and long-term investment are key factors in the successful implementation of this technology.  This study concludes that QKD is a promising security solution for the banking sector in facing future quantum computing threats, although its adoption requires strategic planning, technological readiness, and comprehensive policies.